2006
DOI: 10.1083/jcb.200605050
|View full text |Cite
|
Sign up to set email alerts
|

PGE1 stimulation of HEK293 cells generates multiple contiguous domains with different [cAMP]: role of compartmentalized phosphodiesterases

Abstract: There is a growing appreciation that the cyclic adenosine monophosphate (cAMP)–protein kinase A (PKA) signaling pathway is organized to form transduction units that function to deliver specific messages. Such organization results in the local activation of PKA subsets through the generation of confined intracellular gradients of cAMP, but the mechanisms responsible for limiting the diffusion of cAMP largely remain to be clarified. In this study, by performing real-time imaging of cAMP, we show that prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
190
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(212 citation statements)
references
References 54 publications
13
190
5
1
Order By: Relevance
“…This indicates that a specific compartment deep inside the cell might have a privileged access to the pool of cAMP formed after stimulation of a particular membrane receptor, thereby sensing higher second messenger levels compared with the bulk cytosol due to a PDEdependent 'channelling' of cAMP from the membrane to the microdomain. It has previously been shown in HEK293 cells after prostaglandin E 1 stimulation that PDEs act as local sinks that drain cAMP gradients towards specific contiguous subcellular compartments such as the nucleus 30 . This mechanism allows coexistence of multiple microdomains with various cAMP concentrations independently of their distance from the place of cAMP synthesis, which we now show to occur in physiologically most relevant adult cardiomyocytes and to be regulated by the joint action of PDE3 and PDE4 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that a specific compartment deep inside the cell might have a privileged access to the pool of cAMP formed after stimulation of a particular membrane receptor, thereby sensing higher second messenger levels compared with the bulk cytosol due to a PDEdependent 'channelling' of cAMP from the membrane to the microdomain. It has previously been shown in HEK293 cells after prostaglandin E 1 stimulation that PDEs act as local sinks that drain cAMP gradients towards specific contiguous subcellular compartments such as the nucleus 30 . This mechanism allows coexistence of multiple microdomains with various cAMP concentrations independently of their distance from the place of cAMP synthesis, which we now show to occur in physiologically most relevant adult cardiomyocytes and to be regulated by the joint action of PDE3 and PDE4 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They also may induce anxiogenic-like effects and sedation (Heaslip and Evans, 1995;Imaizumi et al, 1994;Silvestre et al, 1999b), although an anxiolytic-like effect also has been reported (Silvestre et al, 1999a). While studies have shown that PDE4D plays an important role in the mediation of antidepressant-like effect (Zhang et al, 2002) and may be involved in memory , the role of PDE4B has not been investigated due to the lack of highly selective inhibitors of individual PDE4 subtypes and the complexity of the PDE4 family in terms of its numerous variants and compartmentation (Conti et al, 2003;Houslay et al, 2005;Terrin et al, 2006). Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…PDE4 subfamilies may exert different functions based on their differential distributions in the brain (Cherry and Davis, 1999;Perez-Torres et al, 2000) and the compartmentation of cAMP signaling, which is controlled by different PDE4s (Baillie and Houslay, 2005;Fischmeister, 2006;Rich et al, 2007;Terrin et al, 2006). While the lack of selective inhibitors of PDE4 isoforms has made it particularly difficult in understanding the roles of PDE4 subfamilies, gene mutation and RNA interference (RNAi) have been shown to be feasible approaches to identifying functions of PDE4 subfamilies and even their variants (Lehnart et al, 2005;Lynch et al, 2005;Terrin et al, 2006;Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, reduced DISC1 binding to the cAMP-specific 3' ,5'-cyclic phosphodiesterase 4B (PDE4B) has been demonstrated. PDE4B is a phosphodiesterase which has been implicated in animal models with learning and memory impairments 44,49,50 . Polymorphisms of PDE4B have been reported to be associated with schizophrenia in human GWAS 51 .…”
Section: Disc1mentioning
confidence: 99%